Economic value of recreation as an ecosystem service in Ayer Keroh Recreational Forest, Malaysia - Matthew, Nitanan Koshy; Ahmad Shuib; Raja Gopal, Nitya Ganeshwaari; Goh, Ie Zheng (MDPI, 2022)
Economic values of various ecosystem services of recreational forests are not well understood in many countries, including Malaysia. Policymakers and resource managers with a lack of such information may make inappropriate decisions to manage forest resources. To address the information problem, this study used data and estimated the economic value of recreation as a cultural ecosystem service of the Ayer Keroh Recreational Forest (AKRF) in Malaysia using the Travel Cost Method (TCM). The study estimated an economic value of USD 20,346/ha/year for cultural services, including recreation. These findings provide some useful information that might be needed for those involved in planning and management for the development of urban forest sites, especially in AKRF.